Clinical and genetic characterization of neonatal non-ketotic hyperglycinemia: a rare case with SLC6A9 gene mutation - Phadke, Abhishek K.; Kumble, Ali; Raikar, Poonam; Jacob, Manju (International Journal of Research in Medical Sciences, 2025)
Nonketotic hyperglycinemia (NKH) is a rare autosomal recessive disorder caused by mutations in the glycine cleavage system (GCS), leading to glycine accumulation in cerebrospinal fluid (CSF) and plasma, with an increased CSF-to-plasma glycine ratio. Typically presenting in the neonatal period, symptoms include lethargy, poor feeding, hypotonia, seizures, and encephalopathy, often resulting in severe neurological impairment. Early diagnosis is vital but challenging due to the rarity and nonspecific nature of symptoms, especially in populations with high consanguinity rates. We report a neonate born to consanguineous parents who developed severe encephalopathy within 48 hours of birth despite normal antenatal and perinatal findings. The infant exhibited poor feeding, seizures, and worsening neurological status. NKH was confirmed by elevated CSF glycine levels and genetic analysis identifying a novel SLC6A9 mutation. This case highlights the importance of considering NKH in neonatal encephalopathy and the need for genetic testing and counseling in at-risk groups.